The effect of the -Zahorik- model on acquiring grammatical concepts among students of the College of Administration and Economics / University of Baghdad - Sabah Al–Tamimi, Rafid (Opción, 2019)
The current research aims to identify the impact of -Zahorik- model in the acquisition of grammatical concepts among students of the Faculty of Man- agement and Economics University of Baghdad and in order to achieve the goal of research; the researcher has developed the following hypotheses:1. There is no statistically significant difference at the level of significance (0.05) between the average grades of students of the experimental group who stud- ied the Arabic language material in -Zahorik- model and the grades of the students of the control group who studied the same subject in the usual way in the dimensional test.2. There is no statistically significant difference at the level of significance (0.05) in the average differences between the grades of the pre and post tests in the acquisition of grammatical concepts among the students of the experimental group who studied the subject of Arabic in the -Zahorik- model.3. There is no statistically significant difference at the level of significance (0.05) in the average differences between the grades of the tribal and dimension tests in the acquisition of grammatical concepts among the students of the experimental group who studied Arabic in the usual way. The current research was limited to a sample of the students of the first stage in the department of statistics in the Faculty of Management and Economics of Baghdad University for the academic year 2018-2019. 1. There is a sta- tistically significant difference between the average grades of students of the experimental group who studied the Arabic language subject in the (Zahorik) model and the grades of the students of the control group who studied the same subject in the usual way in the post test and in favor of the experimental group. 2. There is a statistically significant difference between the aver- age grades of students of the experimental group who studied the subject of Arabic in the model (Zahorik) and the degrees of students of the exper- imental group in the pre application and their grades in the post applica- tion of the test, and this means an acquisition in the grammatical concepts among the students of the experimental group. 3. There is no sta- tistically significant difference between the grades of the students of the control group in the pre application of the grammar test and their grades in the post application of the test, which means that there is no acquisition in grammatical concepts among the students of the control group. In the light of the results of the research, the researcher reached a number of con- clusions, recommendations and proposals.